Kebijakan Evening Hours Perpustakaan Daerah sebagai Upaya Meningkatkan Aksesibilitas Penggunaan Layanan Perpustakaan - Ramadhan, Ndaru; Adinda FA, Jovanscha Qisty (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2024)
Libraries have strategic functions such as centers for information, science, research, recreation, preservation, and other services and even as a means of realizing the SDGs, so the existence of libraries needs to be carefully considered. The aim of this research is to determine the urgency of the evening hours policy in regional libraries in increasing the accessibility of library service users. The method used in this research is descriptive qualitative method with a library science approach, namely library research. Based on research, it is known that several regional libraries managed by local governments implement evening hours policies or increase service opening hours until the evening for some of the services provided. The Balai Layanan Perpustakaan DPAD DIY as a regional library is expected to be able to carry out a study to replicate the implementation of the evening hours policy in order to increase the accessibility of library service users.